Pre-service physical science teachers’ perceptions of decolonizing the science curriculum in South Africa - Gudyanga, Remeredzayi; Legodu, Glen (Edelweiss Applied Science and Technology, 2026)
This quantitative study explores the perceptions of 117 pre-service science teachers regarding decolonizing the science curriculum in South Africa. While national discourse increasingly emphasizes the importance of integrating Indigenous Knowledge Systems (IKS) into science education, limited research exists on how future teachers understand and engage with this goal. Using a quantitative survey and postcolonial theory as a framework, the study assesses participants' conceptual understanding of decolonization, their attitudes toward IKS, perceived readiness to implement change, and anticipated barriers. Participants generally recognized the benefits of IKS in enhancing learner engagement and promoting inclusivity. However, statistical analysis, including t-tests and chi-square tests, shows no significant differences based on gender, academic level, or program type. Most participants expressed limited confidence in practically applying these concepts in classroom settings. The findings suggest that despite ideological support for decolonization, structural challenges such as insufficient training, lack of resources, and limited institutional guidance hinder practical implementation. The study recommends that science teacher education programs strengthen pedagogical approaches to decolonization, incorporate experiential learning, and foster collaboration with local knowledge holders. Moving from theoretical discourse to practice-oriented preparation will better equip future educators to effect meaningful curriculum transformation in science education.